On The Issue of Prevention of Retinal Detachment in Pregnant Women with High Myopia - Guliyeva S. A, (American Journal of Biology and Natural Sciences, 2025)
High myopia in pregnant women significantly increases the risk of retinal complications, particularly peripheral vitreochorioretinal dystrophies (PVCRD) and rhegmatogenous retinal detachment (RRD). This study aimed to determine the incidence of dangerous PVCRD forms, evaluate hemostatic parameters, and define optimal childbirth management strategies for women with high myopia. A total of 24 pregnant women (48 eyes) aged 19–39 years, with refractive error greater than 6.5 diopters, were examined through comprehensive ophthalmologic and hemostatic evaluations. Retinal dystrophic changes were identified as “snail track” dystrophy (18.75%), retinoschisis (14.5%), and focal hyperpigmentation (4.2%). Peripheral laser coagulation (PPLCR) was performed in 43.75% of cases between 21–32 weeks of gestation, though 42% of these patients ultimately required cesarean section due to insufficient chorioretinal adhesion formation. Retinal detachment primarily developed in cases of lattice degeneration, “snail track” dystrophy, and retinoschisis. Timely PPLCR proved effective in preventing RRD and allowed for vaginal delivery in 58% of cases. Mild alterations in the hemostatic system were also noted, particularly elevated soluble fibrin–monomer complexes (SFMC) in patients with combined PVCRD. These findings suggest that careful ophthalmologic monitoring and preventive laser therapy are essential to reduce retinal complications and enable safe natural childbirth among women with high myopia.